The Influence of Some Positive Rest Activities"Muscular Stretching, Foot Tennis" during the Recovery Process on Some Physiological Variables - Aouadi, Chems-Eddine; kabouya , Mouhammed (sports creativity, 2025)
the study aims to identify the influence of positive resting exercises on physiological variables. for this purpose, we used the experimental method on a sample composed of two groups: controlled and experimental. The sample contained 20 players chosen intentionally. To collect data, we used physiological measurement tools before and after the performance, we also used Ruffier test to measure the recovery capacity. After the collection and statistical analysis of the results, we concluded that the use of positive rest exercises has an impact on the physiological variables and the recovery process. On this basis, the study recommends the use of these activities especially during the physical preparation phase and stand for the player’s state during the season through programming tests to care of the health status of the team